2017
DOI: 10.1371/journal.pone.0181828
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography versus magnetic resonance imaging in detecting and grading common extensor tendon tear in chronic lateral epicondylitis

Abstract: ObjectivesTo investigate the diagnostic performance and reliability of ultrasonography (US) in detecting and grading common extensor tendon (CET) tear in patients with chronic lateral epicondylitis (LE), using magnetic resonance imaging (MRI) as the reference standard.Materials and methodsThe study comprised fifty-eight chronic LE patients. Each patient underwent US and MRI. CET status was classified as: high-grade tear (≥50% thickness), low-grade tear (<50% thickness), suspected tear (possible but not evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…US examination results were not compared with magnetic resonance imaging (MRI) findings, and although the sensitivity and specificity of US have been shown to be comparable to that of MRI, it is often felt that MRI should be used to confirm US findings. 1,5,10,12 Thus, the US findings of this study should be interpreted with some reservation, until confirmed with MRI and/or clinical findings. In contrast to previous studies, concerning asymptomatic tendinopathy, participants in this study were recruited after presenting to a foot and ankle clinic.…”
Section: Discussionmentioning
confidence: 74%
“…US examination results were not compared with magnetic resonance imaging (MRI) findings, and although the sensitivity and specificity of US have been shown to be comparable to that of MRI, it is often felt that MRI should be used to confirm US findings. 1,5,10,12 Thus, the US findings of this study should be interpreted with some reservation, until confirmed with MRI and/or clinical findings. In contrast to previous studies, concerning asymptomatic tendinopathy, participants in this study were recruited after presenting to a foot and ankle clinic.…”
Section: Discussionmentioning
confidence: 74%
“…The diagnosis of LE is based primarily on clinical examination, like visual analogy scale (VAS), and often confirmed with diagnostic imaging including conventional ultrasound (US), magnetic resonance imaging (MRI), real-time sonoelastography, etc. for cases of atypical presentation or those resistant to conservative treatment (6,7). Furthermore, imaging techniques provide the information related to the physiopathology of disease condition and determine the radiological severity of LE, and can be essential in assessing the level of impairment, planning treatment strategies, or guiding surgery (5,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, imaging techniques provide the information related to the physiopathology of disease condition and determine the radiological severity of LE, and can be essential in assessing the level of impairment, planning treatment strategies, or guiding surgery (5,8,9). Although MRI has been widely considered as a reliable complementary method for LE assessment, the high cost, lengthy examination time, and several contraindications may limit its widespread use (6). Currently, the US is increasingly playing a vital role in the diagnosis of LE with inexpensive, non-invasive, and dynamic features.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography (US) has a sensitivity of 64.52%, speci city of 85.19%, and an accuracy of 72.73% in comparison to Magnetic resonance (MRI) [28]. MRI is the gold standard for diagnostic imaging of LE, associated lesions, and for excluding differential diagnoses, but its cost is still high compared to other methods.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the gold standard for diagnostic imaging of LE, associated lesions, and for excluding differential diagnoses, but its cost is still high compared to other methods. Its use is relevant, especially in refractory cases, and when it is desired to have a better assessment of the extent of the lesion in the common extensor tendon origin and associated lesion [28].…”
Section: Discussionmentioning
confidence: 99%